Strategi Pengembangan Usaha Tani Ubi Cilembu secara Berkelanjutan - Nida Amani Nurfadliela; Melbi Tanjung (LPPM UNU CIREBON, 2023)
Efforts to develop sweet potato farming in Cilembu Village are a form of adaptation by farmers in facing reduced productivity of the Neerkom variety. This study aims to explain efforts to develop ecological, economic, and socio-cultural factors in order to create sustainable Cilembu sweet potato farming. This research was conducted using qualitative research methods. Data collection techniques were carried out using questionnaires, in-depth interviews with farmers, traders, researchers, and agricultural extension workers from the Sumedang District Agriculture Service, as well as observation and documentation. Development of ecological factors, namely plant age, adaptability, cultivation techniques, physical cassava, and taste of cassava. The development of economic factors includes land area, productivity, production costs, cassava prices, income, and market demand. Development of socio-cultural factors, namely the age of farmers, education, farming experience, and habits. These three factors are interrelated, in which implementation requires good coordination among relevant stakeholders, namely farmers, traders, credit institutions, agricultural extension workers, and agricultural researchers in order to be able to drive sustainable agricultural development, especially in rural areas.